A microprocessor-controlled optical character recognition system for use in the development of reading aids for the blind - Lim, Nathaniel C. (1982)
The objective of this research is to design an operationally viable procedure for the development of a microprocessor controlled system in order to enable the blind to access ordinary printed materials available for the sighted. It would be possible to use recent advances in microelectronics technology for such purpose. Previous solutions convert the printed character's bit pattern directly to a tactile screen. With this approach, the blind will have to remember the small case and capital letters as well as the numerals. The present approach investigates the plausibility of recognizing printed characters by machine, thus, preparing the way for their eventual transformation into a much more suitable display for the blind. A solid state image sensor designed for optical character recognition scans the printed character and its image is electronically converted into a matrix of occupied and unoccupied positions representing the character and its surroundings respectively. The digitized input image is then processed into a succession of stages, which successively preprocesses the character, normalizes its size, and partitions it into pertinent regions where the existence of particular features (pattern primitives) are tested for. The stages are as follows: A) Smoothing & Noise Cleaning B) Thinning C) Figure Framing D) Partitioning the frame into regions E) Feature Extraction F) Recognition. There are 15 features or pattern primitives of the 26 capital letters of the English alphabet and the 10 numerals that are of interest, the recognition scheme is set to recover 2 kinds of information: 1) The occurrence or non-occurrence of these primitives, and 2) The relational and positional constraints they satisfy. The recognition after feature extraction is based on exhaustive elimination by using a decision tree. The software was simulated at the SORD M223 MARK III Z-80 based microcomputer. To the extent to which the data experimented on here are a realistic approximation of real life characters, the success ratios shown here could also apply to real life reading situations. As long as blemishes in the character due to paper and printing imperfections do not deform the figure too much, the recognition scheme seems to work well even under minor deviations in character shapes or even under localized noise.
Mimeographed.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Blind -- Reading; Optical character recognition devices; Reading devices for the disabled